L’espace en poésie – poésie de l’espace : les Fireside Poets - Michel Barrucand (Anglophonia)
The discovery of American space and its impressive size is best expressed through poetical visions. From the beginning, poets have described their environment, following colonial expansion and the progressive settlement of continuous waves of immigration. In the 19th Century, the geographic description took a new direction, symbolized by the westward movement of the frontier and the crossing of the Middle West, whose vast prairies were on the verge of being conquered and destroyed. The Fireside poets wanted to deal with the present but also to hint at a land that was gradually fading away. This analysis of The Prairies, The Song of Hiawatha and Snow Bound shows how Bryant, Longfellow, and Whittier map these American landscapes, express the dreams that they inspire, and relate the myths on which to found the nation’s geographical and social future, a future that would bear the founding marks as indelible scars.